Program “Kampung Emas” Sebagai Upaya Percepatan Penurunan Angka Stunting di Kelurahan Embong Kaliasin, Surabaya - Andriani, Dinda; Irwanto, Bian Shabri Putri (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
The reduction in stunting rates must be more comprehensive in overcoming it, because this case is one of the national priorities in terms of human resource development. So that in handling stunting cases in Surabaya using the "Kampung Emas" program based on strengthening the 5 pillars of handling stunting. The method of this activity is carried out by means of Focus Discussion Group (FGD), mentoring and monitoring of stunting toddlers, education with lecture methods, community visits, and local market surveys. The results of the implementation of the "golden village" program based on the 5 pillars of stunting management include: health cadres and the village have a commitment to resolve stunting cases, 9 children are classified as stunted, increasing the understanding of education participants to 98% after being given education, getting food ideas after surveying the local market, namely cork fish potato sticks and moringa leaves, and moringa leaf pudding as an innovative healthy menu so that stunting toddlers are not bored. From these various activities, it succeeded in graduating 1 child who was classified as stunted.